The legal culture of the European Court of Human Rights - Arold Lorenz, Nina-Louisa (Raoul Wallenberg Institute human rights library ;, 2007)
Without understanding the legal culture of the judges a full understanding of Strasbourg's rulings seems hardly possible. Through interviews, field observations and case law analysis, this book aims to fill this need and offers a fresh approach towards convergence in Europe.